Studies on nonlinear robust tracking control for a quadcopter system - Saenz Acuña, Johnny Henry (2017)
This thesis presents the modeling and control of a quadcopter vehicle and the application of adaptive backstepping for attitude stabilization. This nonlinear technique has been chosen because they can explicitly address the specific nonlinear dynamics of the plant. The objectives are to derive, validate, simulate and implement this Backstepping controller with a suitable quadcopter model. First a modeling process was conducted using the Newton-Euler formalism together with Euler angles to parameterize the rotations. The subsequently proposed approach consists on the nominal backstepping attitude controller which regulates the pitch , roll and yaw rotations and the adaptive scheme which estimates the external disturbances. Simulations showed satisfying performance in attitude stabilization under uncertainties of up to 50% in inertia matrix and constant external disturbances. Finally the controller is implemented in the real platform based on Odroid single board computer and it showed an overall performance with room to further improvements. Then this work proves that the proposed controller can be successfully implemented.